How BIM Contributes to a Building’s Energy Efficiency throughout Its Whole Life Cycle: Systematic Mapping - Tatjana Vilutienė; Rasa Džiugaitė-Tumėnienė; Diana Kalibatienė; Darius Kalibatas (Energies, 2021)
This paper presents a systematic mapping (SM) study with the aim to determine how Building Information Modeling (BIM) methodologies and technologies contribute to energy-related analyses over the course of the entire building life cycle. The method adopted in the study is based on a set of seven research questions. We used a mixed technique combining co-citation analysis and bibliographic coupling in order to analyze the publications’ datasets for the period 2010–2020. The main advantage and novelty of this study are that the joint dataset from the Scopus and Web of Science databases was used to develop the keyword map. The main findings of this study indicate that many BIM-based applications can be used to analyze the building energy performance at all stages of the building life cycle. However, the applications of BIM in conjunction with other information technologies are limited and are still in the initial stage. In the future, the main improvements should be focused on process, model, system, tool, use and information modeling. The most promising long-term solution is an open BIM framework based on open standards, which allows the integration of BIM and energy simulation tools and satisfies specific data exchange requirements.